The Effect of Alpha s1 Genotype on Some Physiological and Chemical Milk Characteristics in Garganica Goat - Santillo, Antonella; Ciliberti, Maria Giovanna; d’Angelo, Francesca; Albenzio, Marzia (Frontiers in Animal Science, 2022)
In the present study individual milk samples were collected from 80 Garganica goats and the population was genotyped for CSN1S1. Seven different alleles were observed with the A allele found as predominant, followed by the F and B allele, and 14 different genotypes were observed. A proteomic approach was used to classify the individual milk on the basis of protein abundance: four levels of αs1-casein (CN) expression were identified as high (HAS-1), intermediate (IAS-1), low (LAS-1), and null (NAS-1). The present paper aimed to investigate the influence of the level of expression of αs1-casein fraction in milk on proteolytic activities, chemical composition, and renneting properties of individual Garganica goat milk. Results from the present study evidenced that the level of expression of αs1-casein fraction in Garganica goat milk affected chemical composition, curd firmness, and indigenous proteolytic enzymes. In particular, fat, protein, and casein content were higher in HAS-1 and IAS-1 compared to LAS-1 and NAS-1. The SCC decreased passing from the HAS-1 to the NAS-1 and the curd firmness displayed the highest value in HAS-1. The activity of plasmin (PL) was higher in HAS-1 and IAS-1 groups compared to the LAS-1 and NAS-1; whereas, PL plasminogen-derived (PG) activity was the highest in NAS-1 group. On the contrary, the activity of elastase was the highest in LAS-1, intermediate in the IAS-1 group, and the lowest in HAS-1 and NAS-1 groups. Present data demonstrated that the level of synthesis of αs1-CN reflects the efficiency of the mammary gland in the activation of the cellular mechanisms and influences the proteolytic activity in milk, especially the PL-PG system.